Pengembangan Media Pembelajaran Google Site Pada Materi Sistem Ekskresi Kelas XI SMAS Semen Tonasa - Nurdin, Diah Pratiwi; Maulana, Andi; Arif, Wiwin Pramita (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
The objectives of this study are (1) to develop Google Site learning media for the excretory system material for grade XI SMAS Semen Tonasa, (2) to assess the validity, practicality, and effectiveness of Google Site learning media for the excretory system material for grade XI SMAS Semen Tonasa. In its implementation, this study applied a Research and Development (R&D) approach based on the 4D model. This model consists of four stages, namely: (1) Analysis, (2) Design, (3) Development, and (4) Dissemination. The techniques applied include data validity testing using validation sheets, practicality testing through student and teacher response questions, and effectiveness testing through student learning outcome tests. Based on the test results, the following was obtained: (1) The development of Google website-based learning media was carried out by applying the 4D development model, (2) The validation results showed that the developed Google Site learning media obtained an average score of 3.65, which is categorized as highly valid, (3) Meanwhile, the practicality level of the media reached an average of 3.57, which is categorized as very practical, (4) The developed Google Site learning media showed an average effectiveness level of 87.8, which indicates that the learning environment provided was proven to be very supportive of the learning process. Based on the findings of this study, it can be concluded that Google Site-based learning media is valid, practical, and effective for use in teaching and learning activities.